2010
DOI: 10.1097/ico.0b013e3181cb410b
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Keratoconus With Immune Disorders

Abstract: Some strong associations between KC and several immune conditions of autoimmune diseases and allergic IDs may point to the role of the immune system in the pathogenesis of KC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
3
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(89 citation statements)
references
References 32 publications
4
77
3
5
Order By: Relevance
“…109 Normal corneal homeostasis exploits active and passive mechanisms that aim to preserve a hypo-immune status; for instance, the cornea lacks blood and lymphatic vessels. 110 The complex interplay of 113 Even in atopic KC patients, cornea buttons display virtually no eosinophils.…”
Section: Cellular Inflammatory Mediators In Keratoconusmentioning
confidence: 99%
“…109 Normal corneal homeostasis exploits active and passive mechanisms that aim to preserve a hypo-immune status; for instance, the cornea lacks blood and lymphatic vessels. 110 The complex interplay of 113 Even in atopic KC patients, cornea buttons display virtually no eosinophils.…”
Section: Cellular Inflammatory Mediators In Keratoconusmentioning
confidence: 99%
“…In severe cases, where scarring and fibrosis exist, keratoplasty serves both as an optical/refractive treatment and as a means to halt disease progression. 13 Allergic diseases, 16 such as asthma, atopic dermatitis, and allergic rhinitis, are characterized by a hypersensitivity reaction to an allergen. These diseases are very common, with prevalence estimated as 13% of the American population for asthma, 17 17% for atopic dermatitis, and up to 16% for allergic rhinitis.…”
mentioning
confidence: 99%
“…19 However, the studies that examined this association used a relatively small sample size 20,21 or found a relatively weak association. 16 Allergic conjunctivitis (AC), 20 with signs and symptoms ranging from simple intermittent tearing, itching, or hyperemia to severe sight-threatening corneal complications, affects approximately 25% of the world population. Vernal keratoconjunctivitis (VKC) is a seasonally exacerbated allergic inflammation of the ocular surface, involving tarsal and/ or bulbar conjunctiva particularly seen among children and young adults living in regions with hot and dry climate, such as the Middle East.…”
mentioning
confidence: 99%
“…This observation was noted in other studies that we performed [20]. We are not aware of any association between Ashkenazy patients and renal disease.…”
Section: Why Is Keratoconus Associated With Renal Disorders?mentioning
confidence: 50%